The Counselling and psychotherapy research handbook - Vossler, Andreas; Moller, Naomi (SAGE, 2015)
Setting the scene. Why research matters/ Andreas Vossler, Naomi Moller & Mick Cooper -- Attitudes to and perceptions of research/ Andreas Vossler & Naomi Moller -- Beginning the research journey -- Choosing a research question/ Elaine Kasket -- How to read and understand research/ Elena Gil-Rodiguez -- Doing a literature review/ Meg Barker -- Introduction to research methodology/ Ladislav Timulak -- Planning your research: Design, method and sample/ Terry Hanley, Clodagh Jordan & Kasia Wilk -- Ethical considerations/ Tim Bond -- Writing a research proposal/ Mark Donati -- Methodologies and methods for doing research -- Quantitative methods/ Elspeth Twigg -- How to use t-tests to explore pre-post change/ Elspeth Twigg & Paul Redford -- Qualitative methods Linda Finlay -- How to use thematic analysis with interview data/ Virginia Braun, Victoria Clarke & Nicola Rance -- Case studies methodologies/ Julia McLeod, Mhairi Thurston & John McLeod -- How to use case study methodology with single client therapy data/ Mhairi Thurston, Julia McLeod & John McLeod -- Completing the research journey -- Dissemination of research/ Andrew Reeves -- Student top tips/ Brian Sreenan, Harriet Smith & Charles Frost -- Next steps. Building on and using research in training and practice/ Peter Stratton, Naomi Moller & Andreas Vossler.